2014
DOI: 10.1530/jme-13-0274
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR EVOLUTION OF GPCRS: Somatostatin/urotensin II receptors

Abstract: Somatostatin (SS) and urotensin II (UII) are members of two families of structurally related neuropeptides present in all vertebrates. They exert a large array of biological activities that are mediated by two families of G-protein-coupled receptors called SSTR and UTS2R respectively. It is proposed that the two families of peptides as well as those of their receptors probably derive from a single ancestral ligand-receptor pair. This pair had already been duplicated before the emergence of vertebrates to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 211 publications
(256 reference statements)
4
78
0
3
Order By: Relevance
“…Using this approach, it was found that the URP1 and URP2 genes, although present only in fish, emerged long before the tetrapod/fish split and thus represent two distinct paralogous genes, in addition to the UII and URP genes. As mentioned in section II.C, a true ortholog of the URP gene does also exist in teleosts and was recently characterized (Quan et al, 2012;Tostivint et al, 2014). As in tetrapods, teleost URPs possess a single residue extension at their C terminus.…”
Section: Urotensin II and Urotensin Ii-related Peptide In Tumor Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using this approach, it was found that the URP1 and URP2 genes, although present only in fish, emerged long before the tetrapod/fish split and thus represent two distinct paralogous genes, in addition to the UII and URP genes. As mentioned in section II.C, a true ortholog of the URP gene does also exist in teleosts and was recently characterized (Quan et al, 2012;Tostivint et al, 2014). As in tetrapods, teleost URPs possess a single residue extension at their C terminus.…”
Section: Urotensin II and Urotensin Ii-related Peptide In Tumor Cellsmentioning
confidence: 98%
“…In tetrapods, the coding sequence of URP is located in the fifth exon , whereas, in teleosts, it is split between exons 4 and 5 (Quan et al, 2012). As mentioned above (see section II.J), two additional paralogous genes of the UII family have been characterized in actinopterygians and sarcopterygians and have been called URP1 and URP2 (Nobata et al, 2011;Tostivint et al, 2013Tostivint et al, , 2014. In zebrafish, both URP1 and URP2 genes contain five exons and, for each gene, the coding sequence of the mature peptide is located on the last exon (Parmentier et al, 2011).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…Somatostatin has been of interest to researchers due to not only its important function on the regulation of growth (Melmed et al, 1996), but also the complex evolution history of its family genes in vertebrates (Tostivint et al, 2008(Tostivint et al, , 2014. The latest round of whole-genome duplication which has been estimated to have occurred approximately 8.2 million years ago has caused extensive gene duplications in C. carpio (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two other SS variants, somatostatin 5 (SS5) and somatostatin 6 (SS6) were isolated from zebrafish (Danio rerio) (Liu et al, 2010), then subsequently found in several other fish species Tostivint et al, 2013Tostivint et al, , 2014. All of these mature somatostatins are located at the C-terminal of their precursor proteins (preprosomatostatin, PSS), which are encoded by preprosomatostatin genes (Tostivint et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin and urotensin II are two cyclic neuropeptides that have recently been shown to derive from a single ancestral gene (Tostivint et al 2006). In this review, the authors discuss the evolutionary dynamics of somatostatin/urotensin II peptides and their receptors that have led to the unexpected complexity of these neuroendocrine systems (Tostivint et al 2014). The identification of growth hormone secretagogue receptor (GHSR) and its natural ligand ghrelin is a striking example of the power of target base drug discovery, also termed 'reverse pharmacology', for the development of innovative therapeutic compounds (Kojima & Kangawa 2010).…”
mentioning
confidence: 99%